تصميم بناء مسبق الصنع من طابقين مكون من الفولاذ والبيتون يسمح باستنباط وحدات سكنية متغيرة الشكل والوظيفة تصلح للتشييد السريع وإعادة الإعمار - سلوم, دريد; حسن, نايل (Latakia University Journal -Engineering Sciences Series, 2016)
تتطلب المرحلة التي تعيشها سورية حالياً ابتكار نماذج لوحدات سكنية مختلفة تراعي المتطلبات الوظيفية والمعمارية والأمان مع خصوصية الظروف المحلية والمعيشية. تحقق النماذج المبتكرة حماية العائلة وكسب الوقت واستخدام مواد محلية وإمكانية النقل وإعادة البيع ودعم خطط إعادة الإعمار.يقدم هذا البحث عمل قام الباحثان فيه ولأول مرة في سوريا بتصميم وتصنيع وتركيب بناء مسبق الصنع من طابقين مكون من بلاطات وجدران بيتونية مؤطرة بصفائح معدنية رقيقة وهيكل معدني خفيف الوزن مركب كلياً بواسطة البراغي. تم دراسة وتنفيذ هذا البناء بحيث يسمح باستنباط وحدات سكنية أخرى مستقلة ومتعددة، متغيرة الشكل والوظيفة، تحقق المتطلبات الوظيفية والأمان ومتطلبات التشييد السريع وإعادة الإعمار وسكن الايواء.تم تنفيذ الدراسة وإنشاء خطوط انتاج الوحدات السكنية في مبنى إدارة الشركة العامة للبناء والتعمير بموجب عقد استشارة بين جامعة تشرين (يمثلها الباحثان) والشركة العامة للبناء والتعمير. تم الوصول خلال أقل من عام إلى تصميم وإنتاج أربع وحدات سكنية هي: 1- مبنى متصل مكون من طابقين، 2- وحدة سكن كوارث، 3- وحدة مؤسسة عامة، 4- وحدة المدرسة. تحقق الوحدات السكنية المنتجة كافة المعايير المعتمدة لهذا النوع من البناء.The recent situation in Syria requires the creation of new housing units models take into account the functional, architectural, and safe requirements, in addition to specialty of local and living conditions. The created models must achieve family protection, time gaining, using local materials, ability of transporting, reselling, rapid construction, and supporting reconstruction plans. This paper introduces, for the first time in Syria the study, design, fabricating, and erecting of tow-story precast structure composed of reinforced concrete slabs and walls, and light-weight steel structure fully connected by bolts. This structure was designed and implemented in a way that enables producing varied and multi functional house units achieving safety and functional conditions, and rapid construction and reconstruction requirements.The study was introduced by the authors and it was implemented in the General Company of construction in Lattakia. New production lines of housing units were created from scratch by consulting contract between Tishreen University (the authors) and General Company of construction. In less than one year four housing units were designed and produced:1- tow-story continuous building, 2-disaster housing unit, 3- general marketing unit, 4- school unit. These units achieve all above mentioned requirements.